Change We Can Believe In - Johnson, India R.; Fujita, Kentaro (Psychological Science, 2012)
People are motivated to defend and rationalize the status quo, a phenomenon known as system justification. We propose the existence of a second, countervailing system-level motivation: system-change motivation, which is concerned with bettering the status quo over time. The opportunity to receive diagnostic information about the status quo pits the two system-level motives against each other. Whereas system justification promotes a preference for positive information about the status quo, system-change motivation promotes a preference for negative information about the status quo. In three experiments, we found that people preferred negative over positive feedback about the status quo when it was presented as being changeable. Our findings are the first to suggest the operation of a system-change motive.